Assessment of litterfall in the edge of forest fragments at different successional stages in the Atlantic Forest of Rio Grande do Norte, Brazil - Câmara, Yasmim Borges; Holanda, Alan Cauê de; Costa, Emanoelle Josephine Pereira da (Instituto de Ecología, A.C., 2021)
Litter is the most superficial layer of the forest floor, and analyzing its deposition is essential to assess the stability of one of the main routes of nutrient cycling in forest fragments. The objective of this work was to evaluate the litter input on the edge of three forest fragments in different succession stages (transitional and mature) located in the Floresta Nacional de Nísia Floresta (Rio Grande do Norte, Brasil). 54 collectors were installed, 18 in each fragment, spaced from 0 m to 100 m in relation to the edge and, monthly, for 12 months, all the litterfall was collected. The material was oven-dried at 65 °C for 48 hours and weighed on a precision scale. The estimated annual deposition in the internal edge gradient was 3227,90 kg ha-1 (fragment I), 3315,60 kg ha-1 (fragment II) and 1775,90 kg ha-1 (fragment III). Only for fragment III, there were statistical differences in the total input of dead organic matter from the edge to the interior, with values ranging from 93,87 kg ha-1 year-1 (edge) to 261,7 kg ha-1 year-1 (100 m). The largest amount of organic material in fragment II was, at first, due to the diversity of species and the larger size of adult individuals. The litter input had a seasonal behavior, showing greater deposition in the adverse period, indicating that rainfall acts as a regulating agent for such material. In addition, the edge of forest fragments at an early stage of succession tends to deposit less litter on the forest floor.